Dignidade da pessoa humana: concepção e dimensão jurídico-constitucional - Groberio, Sonia do Carmo (2005)
The dignity of the human being has been considered by indoctrinators as an intrinsic and nondissociable quality of any and all human beings and, in spite of the constitutionalization of the term, there is much discussion in the doctrine and in the jurisprudence concerning its content and meaning for the judicial order. The aim of this paper is to discuss the judicial-constitutional conception and the dimension of the dignity of the human being, establishing a relationship between the doctrine and its applicability in the decisions of the Brazilian high courts, considering the hypotheses: The principle of the dignity of the human being is not invoked with the degree of normativity that it was granted by the constitution. The relationship of the principle with the fundamental rights is intrinsic and, in spite of being rather juridical autonomous, in practice its applicability becomes subsidiary, being invoked only for the concretization of the fundamental rights. The principle of the dignity of the human being seldom has priority and may be mitigated; The judicial decisions related to the dignity of the human being are very diversified. The bibliographic research was carried out in the doctrine and the documental research in the jurisprudence of the Supreme Court of Brazil and in the Superior Court of Justice by means of rulings or decisions issued in the period from 1996 to 2005, with reference to the dignity of the human being. From the research resulted a diversity of concepts and indefinition of the term dignity of the human being, standing out the excessive philosophical valuations of the existing doctrinal conceptions. It became evident that the dignity of the human being as an essential nucleus of the fundamental rights and the existence of the possibility of its relativization by means of the analysis of the concrete cases. The judicial decisions are rather varied and the dignity of the human being is invoked either as a principle, sub-principle or rule. It is also found in the judicial decisions that the dignity of the human being is not applied autonomously, always being linked to fundamental rights, and the normative force of the principle granted or conferred by the judicial order is not recognized.